Statistical methods for discovery sampling. - Koh, Kristine Ai Ping. (2008)
This research project first presents an overview of discovery sampling, a sampling method that can be used in an audit. It also highlights the various probability distributions that are used in fixed sample size discovery sampling, including the hypergeometric, binomial and poisson distribution. The project also discusses the use of sequential sampling approach in discovery sampling and concludes with a recommendation of the most appropriate statistical method.